Ensuring adequate vascular access in patients with major trauma: a quality improvement initiative. Issue 1 (9th January 2018) - Verhoeff, Kevin; Saybel, Rachelle; Mathura, Pamela; Tsang, Bonnie; Fawcett, Vanessa; Widder, Sandy
Abstract : Ensuring adequate vascular access in major trauma patients prior to decompensative physiological processes is crucial to patient outcomes. Most protocols suggest achieving two 18-gauge or larger intravenous lines immediately in patients with major trauma. We discuss a quality improvement approach to ensure that >90% of patients with major trauma (as defined by an injury severity score ≥12) at a level one trauma centre receive timely and adequate fluid access. Applying Donabedian principles for process improvement, we used the Alberta Trauma Registry to perform a 4-month chart audit on patients with major trauma at the University of Alberta Hospital. Background data were supported with a formal root cause analysis to outline the problems and generate plan, do, study and act (PDSA) rapid change cycles. These PDSA cycles were then implemented over the course of 2 months to alter system and personnel barriers to care, thereby ensuring that patients with major trauma received adequate vascular access for fluid resuscitation. This was followed by a 6-month sustainability assessment. The percentage of patients with major trauma who received adequate fluid access went from a mean of 55.5% to >90% in 2 months and was sustained at or greater than 90% for 6 consecutive months. The formal application of quality improvement processes is uncommon in trauma care but is much needed to ensure success and sustainability of quality initiatives. Planning including engagement and prechange awareness is crucial to staff engagement, change, and sustainment. Formal quality improvement and change management techniques can elicit rapid and sustainable changes in trauma care. We provide a framework for change to increase compliance with fluid access in patients with major trauma.